EDUCATION PERSPECTIVE EVALUATING SERVICE SECTORS’S STRATEGIES OF THE THAI GOVERNMENT IN THE DEEP SOUTH OF THAILAND - Chumpon Kaewsom (Universitas Islam Negeri Alauddin Makassar, 2017)
This study examines and analyzes the educational strategies pursued by the Thai government in Thailand with particular focus in the Deep South of the country. Its approach is primarily an eclectic, by concentrating on the strengths and weaknesses of the educational strategies as pursued by Thailand. This paper is divided into five parts. The first part looks at the role of education in resolving the conflict in the region. The second part looks at the integration of Pondok/Islamic educational system into Thai educational system. The third part looks at the Thai government’s effort in rebuilding education in the conflict-affected Area. The fourth looks at the bridging education with peace. The last part looks at the effectiveness/efficiency of the Bangkok government’s educational strategies. The data for this study were collected from both primary and secondary sources and analyzed using qualitative method. The primary sources include documents, SBPAC’s annual reports and press release. In addition, the researcher analyzed the outputs of the SBPAC policy-makers relating to the research topic such as speeches, official correspondences and decisions of the organization relating to the management of the conflict in the Deep South. Interviews with knowledgeable people, prominent political and/or religious leaders, key stakeholders as well as the Thai officials were also conducted. The Secondary sources included books, journal articles, newspapers and reliable websites. The study revealed that the Thai government’s educational strategies in the Deep South have not been very effective because the former has struggled to get better understanding of people and to understand the Muslim’s way of life properly. In addition, the Thai government has not push much effort on getting people participating in generating educational strategies that suitable with the area and completely serves their needs.